The Effect of Water Concentration on Growth Media on Lipid Production by Oleaginous Fungi Isolate BR 2.2 - Lesti, Herin Yoga; Ilmi, Miftahul (Jurnal Riset Biologi dan Aplikasinya, 2022)
Oleaginous fungi are one of the microorganisms that can accumulate a high number of biomasses quickly (within 96-130 hours) and are often used to produce lipids. The growth of fungi depends on the chemical composition of the environment in which it grows. The growth media of fungi must contain high carbohydrates as a source of nutrients and high nitrogen content. One of the carbon sources that fungi can use in the growth process is glucose. BR 2.2 isolate is an oleaginous fungus capable of accumulating 28.44% lipids from the total dry biomass with glucose as a carbon source in 50 mL of growth media. Therefore, this study was conducted to determine the effect of variations in the volume of media and incubation time on the production of biomass and lipid isolate BR 2.2. Biomass and lipid production were analyzed at media with additional water volumes of 10, 20, 30, 40, and 50 mL with 48, 96, and 144 hours of incubation times. The results showed that lipid accumulation and biomass production increased with the reduction of water content in the growth media and reached the highest number in the media volume of 20 mL with an incubation time of 144 hours, i.e., 0.87±0.04 g/L and 12.53±0.29 g/L. It can be concluded that biomass and fungal lipid increased along with incubation time and nutrient concentration.